Pengembangan Media Bimbingan Dan Konseling Berbasis Podcast Persiapan Karir - Sakerebau, Desti Marnida; Berdikariyanto, Esrabella Putri Maharani; Windrawanto, Yustinus; Agustin, Adhi Krisna Maria (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
This study aims to develop guidance and counseling media, especially media as a form of interaction in improving student understanding and the skills of BK teachers in delivering material to students. The background of this study is that many students are still confused in determining career choices. The method used in this study is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The final product is a podcast